Museum to Scale 1/7. - Peters, Ewald; Van Mol, Dennis (Brussel : UPA - University Press Antwerp, 2023)
Alechinsky, Pierre ; Arocha, Carla ; Schraenen, Stéphane ; Bellinkx, Ruben ; Bernier, Pascal ; Bervoets, Fred ; Bijl, Guillaume ; Bogart, Bram ; Boon, Elke Andreas ; Borghouts, Karin ; Braeckman, Dirk ; Broodthaers, Marcel ; Buggenhout, Peter ; Bytebier, Jean-Marie ; Charlier, Jacques ; Cole, Stijn ; Copers, Leo ; Crabeels, Cel ; d'O, Honoré ; Danckaert, Bert ; de Beer, Geoffrey ; De Beukelaer, Sergio ; De Beul, Bert ; De Boeck, Lieven ; De Cock, Jan ; De Cupere, Peter ; De Gobert, Philippe ; De Lepeleire, Damien ; De Meyer, Peter ; De Sauter, Willy ; Deleu, Luc ; Delrue, Ronny ; Delvoye, Wim ; Denmark ; Devriendt, Robert ; Eerdekens, Fred ; Ervinck, Nick ; Fabre, Jan ; Francis, Filip ; François, Michel ; Janssens, Ann Veronica ; Kamagurka ; Kiefer, Gideon ; Lafontaine, Marie-Jo ; Lerooy, Thomas ; Liekens, Tom ; Maes, Chantal ; Maieu, Frank ; Martin, Kris ; Meuris, Wesley ; Misonne, Léonard ; Mouffe, Michel ; Muller, Sofie ; Muyle, Johan ; Naveau, Nadia ; Op de Beeck, Hans ; Pacquée, Ria ; Panamarenko ; Quinze, Arne ; Robijns, Gert ; Rogiers, Peter ; Rombouts, Guy ; Schacht, Kelly ; Stallaerts, Helmut ; Boy & Erik Stappaerts ; Strik, Elly ; Swennen, Walter ; Tahon, Johan ; Theys, Koen ; Timmermans, Ante ; Tuymans, Luc ; Van Akoleyen, Stefaan ; Van Beirendonck, Walter ; Van Bossche, Guy ; Van Breedam, Camiel ; Van de Moortel, Joris ; Van de Velde, Rinus ; Van den Broek, Koen ; Van Doorslaer, Etienne ; van Gestel, Fik ; Van Hoeydonck, Paul ; Van Imschoot, Jan ; Van Innis, Benoît ; Van Kerckhoven, Anne-Mie ; Van Oost, Jan ; Van San, Tamara ; Van Severen, Hannes ; Van Snick, Philippe ; Vanden Meersch, Els ; Vandenbranden, Guy ; Vanfleteren, Stephan ; Vanmechelen, Koen ; Vanriet, Jan ; Vercammen, Wout ; Vergara, Angel ; Vertessen, Liliane ; Wauman, Andy ; Wright, Cindy ; Zoete, Dirk
boek